The Jugular Foramen is Rather a Canal With Distinctive Morphological Configuration Concerning Its Clinical Anatomy and Surgical Implications: Morphological Analysis - Al-Redouan, Azzat; Racanska, Michaela; Oliveira, Isabela M C; Oni, Oluwatoba Mark; Vanatkova, Veronika; Musilová, Barbora; Bacar, Zahrah Issufo; Salavova, Sarka; Joukal, Marek; Kachlik, David (Operative neurosurgery (Hagerstown, Md.), 2025)
BACKGROUND AND OBJECTIVES: The jugular foramen (JF) is rather a complex anatomical structure with internal configuration. Its osteomorphology was assessed to redefine this rather long bony passage as a jugular canal (JC) based on its morphometric data. METHODS: The JF was endocranially and exocranially observed and measured by a digital Vernier caliper bilaterally in 402 dry skulls with opened cranial cavity. The following parameters were measured and analyzed statistically: (1) external and internal widths in the mediolateral dimension, (2) external and internal lengths in the anteroposterior dimension, and (3) depth between the external and internal planes of the foramen. The JF/canal was classified based on its appearance and its morphometric features. RESULTS: The mean length of the JC was approximately 12 mm (12.25 mm-right, 11.76 mm-left) and was longer on the right side (P = .05, 95% CI). Its external opening was found to be slightly larger than the internal opening (P = .07-right, P = .06-left). The JC took 3 distinctive course patterns of straight (47.6%), curved (45.5%), and angulated (6.9%). Its openings exhibited 3 types based on their morphometric analysis: 14.4% Type-I (width = length ±1 mm), 9.8% Type-II (width > length), and 75.9% Type-III (width < length). The size of the external opening into the JC was larger than its internal opening (straight: P = .08-right and P = .07-left), (curved: P = .03-right and P = .03-left), (angulated: P = .03-right and P = .04-left). CONCLUSION: The JF should be regarded clinically as a canal. It is composed of internal and external openings where the jugular fossa resides in between. The provided osteomorphological variations of the JC would enhance the diagnostics and surgical planning in JF syndromes radioimaging and surgical interventions.
Keywords: Jugular foramen; Jugular foramen syndrome; Jugular canal; Skull base